The mediation role of work–family conflict in the effect of workplace violence on job satisfaction and intention to leave: a study on health care workers in Turkey - Tutan, Abdulhamit; Kökalan, Özgür (Frontiers in Psychology, 2024)
Background This study aims to determine how workplace violence experienced by healthcare workers in Turkey affects their job satisfaction and intention to leave. It also examines the mediating role of employees’ work-family conflict between these effects. Methods The PROCESS method was used in the study. The research was conducted on 595 health workers in three public hospital affiliated with the Istanbul Provincial Health Directorate. The convenience sampling method was used in the selection of the participants. Results As a result of the analysis, it was determined that there is a positive, significant, moderate (R = 0.35, p < 0.01) relationship between workplace violence and work-family conflict, and a negative, significant and weak relationship between workplace violence and job satisfaction (R = −0.27, p < 0.01), there is a positive, significant, and weak (R = 0.26, p < 0.01) relationship between workplace violence and intention to leave. In addition, there is a negative, significant, and weak (R = −0.27, p < 0.01) relationship between work-family conflict and job satisfaction, and a positive, significant, and weak (R = 0.28, p < 0.01) relationship between work-family conflict and intention to leave. Workplace violence had significant and negative effects on the employees’ job satisfaction and significant and positive effects on the intention to leave and work-family conflicts. Discussion As a result of the mediating variable analysis, it was determined that work-family conflict has a partial mediator role in the relationship between workplace violence, job satisfaction, and intention to leave. The results are very important, especially for managers working in the healthcare sector. Reducing workplace violence against healthcare personnel will contribute to increasing productivity in the sector and providing better quality service to the healthcare sector.